Analysis of Sexual Education Knowledge in Children of Elementary School - Syifa Delaneira Oktora; Heri Yusuf Muslihin; Elan Elan (STKIP Taman Siswa Bima, 2023)
ex education in Indonesia is still controversial, there are still many members of society who do not approve of sex education at home or at school. In general, society's view of sex education is something that is considered